The Angin of the Dalang in the Kelantan shadow play / Maszalida Hamzah - Hamzah, Maszalida (Institute of Graduate Studies, UiTM, 2014)
It is said that the journey of the Dalang of the Kelantan Shadow play is first and foremost determined by the existence of the Angin in him for without which, this vocation will not materialise. Once confirmed, he will undergo the basic, intermediate and advanced level of the ‘Way of the Dalang’. There are twelve types of Angin in the human that is divided into three. First is the Angin found in all Malay traditional arts inclusive of Wayang Kulit and Mak Yong. It is also present in the traditional Kelantan arts through lineage that includes Dalang Wayang Kulit (Malay Shadow play Dalang), Bomoh (healer) or Dukun, Bidan (midwife), Tukang Urut (masseur). The third is the Angin called Saka and this seem to point to the darker side of the Angin. This thesis is concerned only with the first and the second type of Angin while acknowledging the existence of the third. Angin is also said to be a concept of energy or soul or semangat, or nafsu that could also lead to pity or belas and intense pleasure or as an artistic temperament.